Trust in the law but beware!: the possible corruptogenic effects of the law on public procurement in Malawi - Nkhata, Mwiza Jo (Crime, law and social change, 2024)
The persistence of corruption in Malawi is well documented as are its heinous effects. Malawi’s response to combating corruption has involved the adoption of legislation and the establishment of a dedicated agency for dealing with the vice. These efforts notwithstanding, the fight against corruption continues to be a lopsided undertaking with the country registering negligible commendable progress while reports of serious corrupt practices are a regular occurrence. Corruption in Malawi, arguably, has become systemic. Corruption seems particularly rife in the realm of public procurement. This paper posits that while the law may commonly be invoked in aid when tackling corruption, it is important to critically reflect on its contribution in fostering and/or enabling corruption. By specifically focusing on the law on public procurement, the paper demonstrates that this regime of law, by containing ambiguous terms, giving public officials broad discretion, conferring public officials with overboard freedom to create subsidiary legislation or regulations, creating burdensome processes, having lacunas in regulatory or administrative procedures, and giving certain groups preferential treatment during procurement processes motivates, enables and creates opportunities for corruption. As a possible solution, the paper proposes that Malawi should adopt corruption proofing of legislative enactments as an ex ante mechanism for dealing with corruption to supplement investigations and prosecutions, which are ex post facto procedures.